Pengembangan LKPD dengan Menggunakan Media Monopoli Papan Kayu Rekayasa (Mokaya) Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SD/MI - Evita Widiyati Widiyati; Iis Daniati Fatimah; Ariga Bahrodin Bahrodin (Jurnal Tunas Pendidikan, 2023)
Natural science is an attempt to understand nature properly using procedures and reasoning to get a conclusion. In science learning, of course, requires teaching materials. The teaching material in question is to use LKPD. The purpose of this development research is to find out the effectiveness and practicality of using LKPD using engineered wood monopoly media (mokaya). This research is research and development using the ADDIE development model with stages namely analysis, design, development, implementation, and evaluation. ). Collecting data using the method of learning achievement tests, questionnaires, interviews and documentation. The data analysis technique used was the validity score test, practicality, N-gain and student response questionnaire score test. Based on the results of the calculation of the student test results with the information that if the N-Gain index is in the range of values 0.3≤Ng ≥0.7 then the interpretation or statement is moderate. From these results it can be concluded that by using LKPD with mokaya media, it can improve student test results. LKPD using mokaya media fulfills the criteria of being effective and can be used in the science learning process in elementary schools/Madrasah Ibtida'iyah.Keywords: content, formatting, article.